The effect of "clinical virtual round" on clinical self-efficacy among midwifery students - Ghazal Naysanian; Elahe Kardan; Soheila Mohamadirizi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: One of the methods of clinical education is clinical rounds which makes students more skilled in the comprehensive care of patients. since midwifery students are faced with low-risk and high-risk cases of mothers during the perinatal period, Therefore, it is necessary to pay attention to their clinical self-efficacy. The aim of this study was to determine. The effect of "clinical virtual round" on clinical self-efficacy among midwifery students. MATERIALS AND METHODS: The study was experimental with the control group design. The subjects were randomly divided into the intervention (n = 30) and control (n = 30) groups. two groups received clinical virtual round and report back model (respectively). subjects in both groups responded to the 20-item clinical self-efficacy Questionnaire, before and after the intervention. Data were analyzed with paired t-test and t-student by SPSS v 22. RESULTS: The baseline mean ± SD scores for clinical self-efficacy in interventional and control groups were 10.1 ± 1.32, and 10.1 ± 3.05 respectively (P = 0.233). clinical virtual round increased clinical self-efficacy (65.1 ± 1.42) of midwifery students compared with the control group (11.1 ± 1.72) (P = 0.002). CONCLUSION: According to this study's results, it is recommended that clinical virtual rounds can be increasing clinical self-efficacy among midwifery students.